Toward a Voice-Centered Relational Anti-Racist Listening Praxis in Counselor Education - Michelle R Bertrand (Teaching and Supervision in Counseling, 2021)
Abstract This article outlines key elements of an anti-racist listening praxis in counselor education. It demonstrates how racism in relationships of teaching and learning impacts racialized subjectivities, and the personal, cultural and ancestral worlds these subjectivities articulate, in a way that limits the capacity of racialized practitioners to be relational subjects and uses them instead to reinforce White/Western normativity. It describes a way of both listening to and challenging these impacts by re-centering the “I” of racialized speakers and the personal, cultural and traditional knowledges, identities and preferred ways of being to which they refer in their stories. Examples of the listening praxis are offered. Practical applications in research and methods of teaching and learning in counselor education are considered.
Keywords: racialized subjecthood; self-alienation; anti-racist listening